2018
DOI: 10.1080/21688370.2017.1404189
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the gap: Super-resolution microscopy of epithelial cell junctions

Abstract: Cell junctions are critical for cell adhesion and communication in epithelial tissues. It is evident that the cellular distribution, size, and architecture of cell junctions play a vital role in regulating function. These details of junction architecture have been challenging to elucidate in part due to the complexity and size of cell junctions. A major challenge in understanding these features is attaining high resolution spatial information with molecular specificity. Fluorescence microscopy allows localizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 113 publications
0
11
0
Order By: Relevance
“…The tight junctions and vascular endothelial cells are important components of the blood labyrinth barrier as well as ion channels [ 30 , 53 57 ]. Our cluster analysis of the RNA transcriptome data from both pigs and mice showed that the tight junctions were significantly different in the stria vascularis of these two species.…”
Section: Discussionmentioning
confidence: 99%
“…The tight junctions and vascular endothelial cells are important components of the blood labyrinth barrier as well as ion channels [ 30 , 53 57 ]. Our cluster analysis of the RNA transcriptome data from both pigs and mice showed that the tight junctions were significantly different in the stria vascularis of these two species.…”
Section: Discussionmentioning
confidence: 99%
“…This study does not determine the precise subcellular protein localization in human endoneurial microvascular endothelial cells. Immunogold electron microscopy and super resolution microscopy provide avenues to more precisely determine the in situ subcellular localization of specific molecules restricted to the human BNB, particularly components of the restrictive intercellular junctional complex such as CLDN4, or determine the luminal or abluminal localization of transporters such as SLC1A1 prior to functional studies. This is an important future direction.…”
Section: Discussionmentioning
confidence: 99%
“…Immunogold electron microscopy and super resolution microscopy [46][47][48][49] ORCID Eroboghene E. Ubogu https://orcid.org/0000-0002-8307-9994…”
Section: Discussionmentioning
confidence: 99%
“…The tight junctions and vascular endothelial cells are important components of the blood labyrinth barrier as well as ion channels [42][43][44][45][46] . Our cluster analysis of the RNA transcriptome data from both pigs and mice, showed that the tight junctions were significantly different in the stria vascularis of these two species.…”
Section: Discussionmentioning
confidence: 99%